Building Road Safety Institutions in Low- and Middle-Income Countries : The Case of Argentina - Bhalla, Kavi (Taylor and Francis, 2019)
Traffic injuries remain a leading health concern in most low- and middle-income countries (LMICs). However, most LMICs have not established institutions that have the legislative mandate and financial resources necessary to coordinate large-scale interventions. Argentina provides a counterexample. Argentina is a federal country where the decentralization of authority to provincial governments was a key barrier to effective national interventions. In 2008, Argentina passed a law establishing a national road safety agency and subsequently received a World Bank loan to build the agency’s capacity to coordinate actions. Although traffic injuries in Argentina have not yet begun to decline, these developments raise important questions:Why did Argentina come to view road safety as a problem?Why was institutional reform the chosen solution? What was the political process for achieving reform? What are the broader implications for institutional reform in LMICs?We explore these questions using a descriptive case study (single-case, holistic design) of Argentina.